Money Politics and Electoral Clientelism in the 2024 Legislative Election: A Case Study in Malang City - Favian, Dhien (Journal of Politics and Policy, 2026)
This research aims to uncover the transformation of money politics in the 2024 Legislative Election in Malang City. Using the framework of electoral clientelism, this research examines how candidates adapt to tight competition through organized material exchange strategies. The method used is a descriptive qualitative case study approach in two villages in Malang City. Primary data were collected through field observations, participatory monitoring by Malang Corruption Watch (MCW), and in-depth interviews with key informants. The research suggests that money politics in Malang City has evolved from conventional vote buying to "institutionalized clientelism." There are three main modes found: (1) transactional vote buying through cash distribution; (2) relational clientelism through the politicization of social assistance such as PIP scholarships; and (3) programmatic clientelism through the hijacking of aspirational funds for local economic interests. This research also highlights the ineffectiveness of law enforcement due to regulatory gaps in the Election Law and institutional deadlock at the Gakkumdu Center. This systemic failure makes political corruption a legitimate practice for candidates to recoup their electoral investments. Moreover, the emergence of potential digital clientelism, such as the distribution of digital money, has been identified as a new challenge for future election monitoring.